Risk Factors for Development of Endophthalmitis after Open Globe Injury in Children: A Case-Control Study. (17th November 2022) - Sen, Pradhnya; Kohli, Gaurav Mohan; Shah, Chintan; Mohan, Amit; Tiwari, Amrita; Ingale, Rashmi; Shenoy, Pratik; Sen, Alok
ABSTRACT: Aim: To identify risk-factors for developing endophthalmitis following open globe injury (OGI) in children. Methods: Retrospective, single-center, case-control study of children aged <18 years who sustained OGI. Results: Our cohort of 93 eyes consisted of 30 cases (Group A- endophthalmitis) and 63 controls (Group B- no endophthalmitis). Twenty-four eyes (80%) diagnosed with endophthalmitis presented after 24 hours of injury. The presence of central corneal zone-1 injuries (Odd ratio [OR]: 6.64, p= 0.001) and vitreous in wound (OR: 3.53) were associated with the risk of developing endophthalmitis. (p= < 0.05) Additionally the presence of iris prolapse (OR: 4.76) and posterior capsular rupture (PCR) (OR: 5.80) increased the risk of developing endophthalmitis.(p <0.05) . Streptococci was isolated in 15 eyes, Pseudomonas in 3 eyes, and Candida in 1 eye. The visual outcomes at three months were significantly worse in Group A (LogMAR 1.77±1.06) compared to Group B (LogMAR 0.65±0.68)(p<0.05). Conclusion: Central corneal involvement, vitreous/ iris incarceration and PCR were important risk factors for development of PTE in children